2007
DOI: 10.1080/00222930701664203
|View full text |Cite
|
Sign up to set email alerts
|

Specialist and generalist species in habitat use: implications for conservation assessment in snakes

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…1 & 2). Species with a narrow and fragmented geographical range (Hanski 1982;Korkeamäki & Suhonen 2002;Segura et al 2007) and occurring in low-quality habitats (e.g., Thomas et al 1996;Johnson 2004;Suhonen et al 2010) have been reported to be sensitive to environmental changes.Several previous studies show that species with limited ecological and geographical range size are vulnerable to extinction (e.g., Johnson 1998;Purvis et al 2000a;Collen et al 2011). Locally, common species become widely distributed because of their low-extinction and high-colonization rates (e.g., Hanski & Gyllenberg 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1 & 2). Species with a narrow and fragmented geographical range (Hanski 1982;Korkeamäki & Suhonen 2002;Segura et al 2007) and occurring in low-quality habitats (e.g., Thomas et al 1996;Johnson 2004;Suhonen et al 2010) have been reported to be sensitive to environmental changes.Several previous studies show that species with limited ecological and geographical range size are vulnerable to extinction (e.g., Johnson 1998;Purvis et al 2000a;Collen et al 2011). Locally, common species become widely distributed because of their low-extinction and high-colonization rates (e.g., Hanski & Gyllenberg 1997).…”
Section: Discussionmentioning
confidence: 99%
“…4 Percentage of P. hispanica and P. algirus in a macrohabitat and b microhabitat types in burnt and unburnt sites features of snakes are unknown, many species combine several traits such as low fecundity, retarded sexual maturity, and small population size, making them vulnerable to extinction (Webb et al 2002). Within snakes, specialist species in the habitat use are more threatened than generalist species (Segura et al 2007), and ambush predators snakes are more commonly threatened than active foragers (Reed and Shine 2002). Within the snake assemblage in the Natural Park, V. latastei is the only ambush predator and the most ecological specialist (Santos et al 2006), factors that probably would explain why it was found more frequently in unburnt than in burnt habitats ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For reptiles and amphibians, the literature on dispersal rates is sparse. However, Segura et al 49 found that snakes have limited dispersal abilities, and Araujo et al 50 with the observed temperature change, and thus providing a lower limit to the potential dispersal rate. However, dispersal in lizards could be inhibited by temperature rise 52 .…”
mentioning
confidence: 99%